FREEDOM TO WORK OR THE RIGHT TO WORK: THE SEARCH FOR OPTIMAL LEGAL WORDING IN THE RUSSIAN CONSTITUTION - A. H. Marulina; L. V. Petrova (Гуманитарные и юридические исследования)
The authors analyze the legal structure of «freedom of labor» used in the Constitution of the Russian Federation, and offer certain steps for legislative consolidation of the subjective right of the individual to work.